2008
DOI: 10.1007/s00404-008-0698-0
|View full text |Cite
|
Sign up to set email alerts
|

A case of benign metastasizing leiomyoma treated by surgical castration followed by an aromatase inhibitor, anastrozole

Abstract: In addition to castration by bilateral oophorectomy or gonadotropin-releasing hormone agonist, the use of aromatase inhibitor is one of the treatment options for the further suppression of peripheral estrogen production in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
31
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 17 publications
1
31
0
Order By: Relevance
“…Immunohistochemistry revealed that most BML tumor cells are positive for estrogen receptor and progesterone receptor; consequently, the disease is considered hormonedependent [2,5,8]. Some authors stated that bilateral oophorectomy should be considered as a treatment in premenopausal patients [10,14]. Ip et al [2] suggested that in patients with symptomatic metastasis, resection should be undertaken whenever possible.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Immunohistochemistry revealed that most BML tumor cells are positive for estrogen receptor and progesterone receptor; consequently, the disease is considered hormonedependent [2,5,8]. Some authors stated that bilateral oophorectomy should be considered as a treatment in premenopausal patients [10,14]. Ip et al [2] suggested that in patients with symptomatic metastasis, resection should be undertaken whenever possible.…”
Section: Discussionmentioning
confidence: 96%
“…GnRH agonist treatment is also predominantly performed against residual tumors or for preoperative tumor reduction. Other therapeutic agents include aromatase inhibitors [9,14], selective estrogen receptor modulators (such as tamoxifen or raloxifene) [9], and progesterone (such as medroxyprogesterone acetate) [5,7,12] in some case reports. Rivera et al [9] reported a clear effect when an aromatase inhibitor (such as anastrozole) was used, whereas a GnRH agonist failed to control tumor progression.…”
Section: Discussionmentioning
confidence: 98%
“…Although LPD is a different entity when compared with UMs, there might be a relation between morcellation of UMs and an iatrogenic development of this disease. Several studies which presented that LPD shrink under sex steroid hormone manipulation, including BSO [53][54][55], menopause [65], megestrol [66], SERM [55], AI [55,67], and GnRHa [55,56,68]. Laparoscopic myomectomy might result in the growth of multiple PM nodules mimicking LPD [31].…”
Section: Discussionmentioning
confidence: 99%
“…Occasionally, pelvic surgery combined with hormonal treatment has been proposed. 17 Other reported treatment methods include chemotherapy, ovarian radiotherapy, pulmonary nodule resection, and careful observation, especially in women in menopause with declining estrogen levels. Most BML lesions remain constant or decrease in size during follow-up after bilateral salpingo-oophorectomy.…”
Section: Discussionmentioning
confidence: 99%